2013
DOI: 10.1530/joe-13-0175
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycotoxins affect scavenger receptor expression and the hormonal profile of female rats

Abstract: The levels of advanced glycation end products (AGEs) are increased under conditions of impaired glucose metabolism and/or oxidative stress, promoting insulin resistance and other endocrine abnormalities. AGEs play a major role in the pathogenesis of several diseases such as diabetes, atherosclerosis, polycystic ovary syndrome and Alzheimer's disease, contributing to progressive ageing. Receptor-based clearance of AGEs by the receptor for AGE (RAGE) and/or the macrophage scavenger receptor A (SR-A) is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 26 publications
(34 reference statements)
1
29
0
Order By: Relevance
“…A study on Wistar rats having highly expressed RAGE in mononuclear cells (peripheral blood) revealed low levels of the hormones, along with high levels of glucose, insulin, and testosterone. This data verified that PCOS is an endocrine disorder that is highly influenced by metabolism and diet [71,92,108]. Increased levels of anti-Mullerian hormones (AMH) have a sustainable effect on the reproductive system by provoking anovulation via direct inhibition of FSH.…”
Section: Ages and Women's Healthsupporting
confidence: 66%
“…A study on Wistar rats having highly expressed RAGE in mononuclear cells (peripheral blood) revealed low levels of the hormones, along with high levels of glucose, insulin, and testosterone. This data verified that PCOS is an endocrine disorder that is highly influenced by metabolism and diet [71,92,108]. Increased levels of anti-Mullerian hormones (AMH) have a sustainable effect on the reproductive system by provoking anovulation via direct inhibition of FSH.…”
Section: Ages and Women's Healthsupporting
confidence: 66%
“…(59,60) Sex hormones may play a role on the AGE-mediated changes in vertebral structure and function observed in this study. Chatzigeorgiou and colleagues (61) found that a high-AGE diet increased serum glucose, insulin, and testosterone levels, as well as decreased estradiol and progesterone levels, suggesting there may exist a metabolic and hormonal dysregulation attributed to high-AGE dietary ingestion. Consequently, this study highlights a need for future investigations to identify sex-dependent tissue and cellular mechanisms for these observed effects and means of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe a significant interaction between CML-AGE and BMI on CRC risk in our study. Because levels of CML-AGE have also been shown to be modulated by its receptors, including galectin 3, macrophage scavenger receptor [57], AGER-1 and sirtuin 1 [58], its full impact at the tissue level may need to be considered in the context of its receptors.…”
Section: Discussionmentioning
confidence: 99%